THE DYNAMICS OF MUHAMMADIYAH ISLAMIC THOUGHT IN RESPONDING TO THE ISSUES OF RADICALISM AND DIVERSE INTOLERANCE; A STUDY OF ISLAMIC TRANSFORMATION IN BIMA - Ihlas; Hendra; Rusmaeni; Andi, Muhammad; Abdullah, Sufarhan; Supriyadin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the dynamics of Muhammadiyah’s Islamic thought in responding to radicalism and religious intolerance in Bima, focusing on the transformation of local religious understanding and the organization’s strategies in promoting moderation and pluralism. The research employs a library research method, collecting and analyzing primary and secondary literature, including Muhammadiyah publications, academic journals, and previous studies, with qualitative content analysis to interpret key concepts, patterns, and strategies. The findings indicate that Muhammadiyah integrates modernist, rationalist, and reformist approaches with local socio-cultural values, implementing educational programs, social initiatives, and theological reinterpretation to foster tolerance and mitigate radical ideologies. Community engagement, inclusive religious activities, and interfaith dialogues contribute to enhancing social cohesion and resilience against extremist influences. The study also highlights Muhammadiyah’s contextually sensitive approach, which adapts programs to local cultural diversity while maintaining universal principles of moderation, distinguishing its model from other organizations. These strategies demonstrate that Muhammadiyah not only functions as a religious institution but also as a proactive intellectual and social actor, offering practical solutions to counter radicalism and promote pluralism. The research provides insights into the role of local Islamic organizations in shaping moderate religious thought and fostering community harmony.